2014
DOI: 10.17221/636/2014-pse
|View full text |Cite
|
Sign up to set email alerts
|

Impact of site-specific weed management in winter crops on weed populations

Abstract: This work is focused on evaluating the effects of site-specific weed management (SSWM) on weed populations over a 4-year period. SSWM was used on a 3.07 ha experimental field during 2011-2014 in a rotation of winter wheat and winter oilseed rape. The area was split into application cells of 6 × 10 m and weed abundance was evaluated manually in each cell. Four different herbicide treatments were tested. Standard whole-field herbicide application (blanket spraying) was treatment 1. Treatments 2, 3 and 4 comprise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Only at the field plot 'Sickte 15' in 2019, the yield was 1.4 t (16%) above the conventional application field plot. In other studies, yield increases by precision agriculture technologies in weed management could also not be clearly observed either in field trials or in model estimations (Gerhards et al, 2011;Hamouz et al, 2013Hamouz et al, , 2014. Hamouz et al (2013) found that site-specific weed management applied to winter cereals and winter oilseed rape had no significant effect on crop yields.…”
Section: Pesticide Savings and Potential Environmental Effectsmentioning
confidence: 88%
See 4 more Smart Citations
“…Only at the field plot 'Sickte 15' in 2019, the yield was 1.4 t (16%) above the conventional application field plot. In other studies, yield increases by precision agriculture technologies in weed management could also not be clearly observed either in field trials or in model estimations (Gerhards et al, 2011;Hamouz et al, 2013Hamouz et al, , 2014. Hamouz et al (2013) found that site-specific weed management applied to winter cereals and winter oilseed rape had no significant effect on crop yields.…”
Section: Pesticide Savings and Potential Environmental Effectsmentioning
confidence: 88%
“…Hamouz et al (2013) found that site-specific weed management applied to winter cereals and winter oilseed rape had no significant effect on crop yields. On the other hand, Hamouz et al (2014) found negative correlation coefficients between plant densities in site-specific weed management treatments indicating that some weeds e.g. Apera spica-venti did not establish a long-term soil seed bank.…”
Section: Pesticide Savings and Potential Environmental Effectsmentioning
confidence: 93%
See 3 more Smart Citations